An Uncommon Presentation Severe Hypercalcemia Linked to Cystic Parathyroid Adenoma Despite Negative Sestamibi Scan: A Case Report - Smriti Acharya; Sharon Daniel; Suyash Acharya; Rajinder Gupta; Daniel Kannappan (Journal of Nepal Medical Association)
Cystic parathyroid adenomas are uncommon occurrences, constituting approximately 1-2%, of primary hyperparathyroidism cases. They frequently pose diagnostic difficulties due to their limited detection in sestamibi scans. These cases of primary hyperparathyroidism commonly manifest with hypercalcemic crisis despite negative scan results. I present a rare scenario involving an elderly male who arrived at the emergency department with a swollen left neck, primarily due to a thyroid cyst causing breathing difficulties. Incidentally, hypercalcemia was also discovered during examination. Thorough investigations ensued, leading to the decision to perform a right hemithyroidectomy to address the large thyroid cyst and a parathyroidectomy. Histopathological analysis confirmed the presence of a cystic parathyroid adenoma, with subsequent normalization of calcium levels. Following the procedures, the patient experienced hypocalcemia and required calcium supplementation. This case stands out due to the high levels of parathyroid hormone, which typically raises suspicion for parathyroid carcinoma, making it a unique diagnostic challenge.